The Causal Relationship between Immune-Mediated Inflammatory Diseases and Aortic Aneurysm: A Bidirectional Two-Sample Mendelian Randomization Study - Sijia Sun; Jie Li; Mengxian Sun; Jie He; Songtao Tan; Ge Wang; Yuan Zheng; Xiaoping Fan (Journal of Immunology Research)
Background and Objective. Observational studies have frequently linked aortic aneurysm (AA) to immune-mediated inflammatory diseases (IMIDs) as a cardiovascular complication. However, the presence of confounding factors has cast doubt on the validity of this association and the potential for reverse causality. This study employs a two-sample bidirectional Mendelian randomization (MR) approach to elucidate the causal relationships between AA and IMIDs. Methods. We sourced genetic association data from public genome-wide association study databases for populations of European ancestry. Adhering to MR principles, we identified valid instrumental variables from genetic variants. A range of statistical methods were applied for MR analysis, with the inverse variance weighted (IVW) method emerging as the most reliable estimator of causality in this context. Results. The causal estimates obtained using the IVW method revealed a significant association between genetically predicted AA and rheumatoid arthritis (RA; OR = 1.06, 95% CI = 1.01–1.12, P=0.029). Conversely, genetically predicted RA showed nonsignificant causal estimates of AA (OR = 0.97, 95% CI = 0.92–1.02, P=0.204). Additionally, there was no evidence to suggest that AA may increase the risk of inflammatory bowel disease (IBD), Crohn’s disease (CD), ulcerative colitis (UC), systemic lupus erythematosus (SLE), and psoriasis (PSO). The sensitivity analysis confirmed the absence of heterogeneity or horizontal pleiotropy effects. Conclusion. Our findings shed light on the causal effects between genetically predisposed AA and RA. They also suggest the potential clinical utility of human leukocyte antigen (HLA) risk genetic markers for developing personalized treatment and prevention strategies.